Labial vitiligo associated with a factice disorder: a case report - Fricain Margaux; Weidmann Pierre; Roche Yvon; Fricain Jean Christophe (EDP Sciences, 2018)
Introduction: Vitiligo is a non-contagious leukoderma. The loss of melanocytes result in a local hypopigmentation like white symmetrical plaques with sharp edges, most of the time surrounded by hyperpigmentation. It might be an auto immune disease with a genetic predisposition linked to psychological disorders. Oral mucosa vitiligo has rarely been described in the literature. Observation: A seventeen years old patient, native from North Africa, has consulted for a half left upper lip depigmentation appeared in October 2016. The dermatologist had made the diagnosis of vitiligo and prescribed vitamin C and folic acid, without any result. In July 2017, as the lesion has extended to the whole upper lip, the patient came to oral mucosa pathology consultation. Anamnesis revealed a chronic lips chewing. Clinical examination revealed a linear vermillion border depigmentation of the upper lip associated with peripheral pigment enhancement, as well as digital cutaneous involvement. The prescribed treatment was: tacrolimus 0.1% twice daily in local application, stopping practice disorder and sun protection. Comment: Diagnosis of vitiligo is based on clinical examination that can differentiate a segmental vitiligo (localized on at least one dermatomes) of a non-segmental vitiligo (acrofacial, generalized, universalis). Vitiligo of the oral mucosa is rare. It has mainly been described in India. Oral mucosa involvement would affect 55% of patient and the lip would be affected in almost one in two cases in this population. Conclusion: Oral mucosa vitiligo must be known by oral surgeon who has to master the diagnosis and treatments in association with dermatologist, given the concomitant skin involvement that is almost mandatory.